The Reliability of the Current Perception Threshold in Volunteers and Its Applicability in a Clinical Setting. (March 2015) - Gaudreault, François; Drolet, Pierre; Fallaha, Michel; Varin, France
<x xml:space="preserve">Abstract</x> BACKGROUND: Even though current perception threshold (CPT) has been used for evaluating the effectiveness of sensory block in patients before surgery, its reliability under controlled conditions has not been investigated. Two independent investigations were performed. The primary objective of the first study was to determine the test-retest reliability of CPT measures after repeated stimulations in a group of healthy volunteers. The primary objective of the second study was to evaluate the clinical applicability of this technique to assess the sensory onset of a femoral nerve block in patients undergoing knee surgery. METHODS: Thirty healthy subjects participated in 2 identical sessions, separated by at least 24 hours, in which CPTs were measured after 5 consecutive stimulations over the anteromedial aspect of the thigh. Similar measures were obtained in 15 orthopedic patients receiving a femoral nerve block with 20 mL of ropivacaine 0.5%. Test-retest reliability was assessed using intraclass correlation (ICC) and standard error of measurement (expressed as coefficient of variation [CVSEM]), whereas Student t test (P < 0.05) compared the increase in CPTs over baseline. RESULTS: Within-day ICC values ranged (% confidence interval [CI]) from 0.66 to 0.95 with a CVSEM of approximately 39% (% CI: 17%–58%). Between-day ICC values, ranging from 0.57 to 0.94 (CVSEM: approximately 45%, % CI: 13%–71%), indicated that day-to-day CPT measurements are also variable. The current intensity needed for sensory perception in orthopedic patients significantly increased, varying from a mean CPT value of 82.5 ± 66.5 μA (SD) at time zero to an average of 481 ± 338 μA, 22 ± 8 minutes after the administration of the local anesthetic. CONCLUSIONS: CPT proved to be a reliable assessment tool for within-day sensory perception in healthy volunteers. Our study also suggests that CPT can be applied to characterize, in a quantitative manner, the sensory onset of a peripheral nerve block in a clinical setting, thereby supporting its use in future studies comparing different regional anesthetic modalities or approaches.